Gateways for consumption: A rhythmanalysis. (August 2019) - Massey, Joanne
This article uses participant observation data to explore teenagers' presence in two urban public spaces in Manchester, England. The urban spaces under investigation are public, but surrounded by retail outlets and act as gateways for consumption. The aim is to answer the question 'how do the rhythms of teenage life differ when ordinary and extraordinary activities occur in urban public spaces of consumption?' Lefebvre's Rhythmanalysis is employed to analyse the data and identify instances of eurhythmia (harmonious rhythms), arrhythmia (discordant rhythms) and polyrhythmia (multiple simultaneous rhythms) during periods of typical and extraordinary use. Ordinarily the teenagers used the spaces of consumption to mostly meet and socialise with friends with a small number of them using the space to skateboard. This occurred harmoniously alongside others who pass through these gateways to consumption indicating multiple rhythms. The findings indicate that the teenagers were displaced from urban space during the staging of official events which involved increased control from authorities such as the local council and police. They were replaced by a different crowd of people consisting of mostly families and adults. Paradoxically, the 'festival' atmosphere created by extraordinary events in the gateways of consumption resulted more interaction among those present despite increased control from the authorities. Rhythmanalysis proved useful in understanding of spaces when researching spaces of consumption, as it exposes the temporal and fluid nature of urban space. Ultimately, there was no room for the presence of regular users (teenagers) during the staging of extraordinary events indicating a lack of multiple rhythms.